Development of Solid Lipid Nanoparticles of Gac (Momordica cocochinensis Spreng) Oil by Nano-Emulsion Technique - Mai, H.C.; Le, T.T.T.; Diep, T.T.; Le, T.H.N.; Nguyen, D.T.; Bach, L.G. (Asian Journal of Chemistry, 2017)
Solid lipid nanoparticles have emerged as a next-generation drug delivery system with potential applications in the pharmaceutical field, cosmetics, research, clinical medicine and other allied sciences. In the present work, gac oil-loaded solid lipid nanoparticles were successfully prepared by a nano emulsion technique employing high-speed homogenizer. In this study, solid lipid nanoparticle were successfully prepared by using Emulgade SE-PFTM lipid, high-speed homogenization with the support of surfactant. The suspensions contained 5 % active agents (gac oil w/w) were dispersed in the presence of surfactant (Tween-80:Span-80 ratio of 72:28 w/w) at the content of 5 % by using the IKA homogenizer at the speed of 10000 rpm for 60 min (30 min hot homogenization and 30 min cold homogenization). The obtained mixture had the median size of 200 nm (by laser diffractometric spectrometry, LSD). Entrapment efficiency was about 90.8 %.